2009
DOI: 10.1098/rstb.2009.0126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, inbreeding and chemical exposure—combined effects in wildlife and critical considerations for ecotoxicology

Abstract: Exposure to environmental chemicals can have negative consequences for wildlife and even cause localized population extinctions. Resistance to chemical stress, however, can evolve and the mechanisms include desensitized target sites, reduced chemical uptake and increased metabolic detoxification and sequestration. Chemical resistance in wildlife populations can also arise independently of exposure and may be spread by gene flow between populations. Inbreeding-matings between closely related individuals-can hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 153 publications
(203 reference statements)
1
69
0
2
Order By: Relevance
“…Keanekaragaman genetik merupakan suatu tingkatan biodiversitas yang merujuk pada jumlah total genetik dalam keseluruhan spesies yang mencakup aspek biokimia, struktur, dan sifat organisme yang diturunkan secara fisik dari induknya (Brown et al, 2009). Faktor-faktor yang sangat berpengaruh terhadap keragaman genetika pada suatu populasi adalah seleksi alam, mutasi, genetic drift, dan perkawinan yang tidak acak (Spielman et al, 2004).…”
Section: Pendahuluanunclassified
“…Keanekaragaman genetik merupakan suatu tingkatan biodiversitas yang merujuk pada jumlah total genetik dalam keseluruhan spesies yang mencakup aspek biokimia, struktur, dan sifat organisme yang diturunkan secara fisik dari induknya (Brown et al, 2009). Faktor-faktor yang sangat berpengaruh terhadap keragaman genetika pada suatu populasi adalah seleksi alam, mutasi, genetic drift, dan perkawinan yang tidak acak (Spielman et al, 2004).…”
Section: Pendahuluanunclassified
“…Genetic variation among populations of the same species might also incorporate the loss of polymorphisms or allozymes associated with altered drug target sensitivity or increased uptake versus loss rate of environmental chemicals, including pharmaceuticals, in a range of wildlife, humans and model species (reviewed in [71]). This presents a potential challenge for read-across which is based on the (often true) premise that related species react similarly to pharmaceuticals [66], as it appears that certain species can be susceptible to pharmaceuticals, even when closely related taxa are not [9].…”
Section: Pharmaceuticals As Environmental Contaminants Of Concernmentioning
confidence: 99%
“…Both abiotic (Brown et al, 2009) and biotic (Schmitt and Ehrhardt, 1990;Botham et al, 2009) factors can contribute to the differential expression of ID across environments. In a review of 34 studies, Armbruster and Reed (2005) found a trend for ID to increase in more stressful environments.…”
Section: Introductionmentioning
confidence: 99%